Geometry/ Ray C. Jurgensen - Jurgensen, Ray C.
Points, lines, planes and angles, undefined terms and basic definitions, introduction to proof, parallel lines and plaes, when lines and planes are parallel, applying parallel lines to polygons, congruent triangles, using congruent triangles, similar polygons, right triangles, circles, tangents, arcs and chords, construction and loci, areas of plane figure, coordinate geometry, tranformations